58th Open Seminar on Acoustics joined with 2nd Polish-German Structured Conference on Acoustics - Salamon, Roman; Kozaczka, Eugeniusz; Grelowska, Grażyna (Archives of Acoustics, 2011)
The 58th Open Seminar on Acoustics and 2nd Polish-German StructuredConference on Acoustics are organized by the Gdańsk Division of the PolishAcoustical Society, the latter jointly with the German Acoustical Society DEGA.These scientific events are going to be held in the Delfin Hotel in Jurata onHel Peninsula on 13 – 16 September 2011.The topics of the papers submitted to the 58th Open Seminar on Acousticscover a large area of theoretical, technical and experimental research in the fieldof acoustics. The 2nd Polish-German Structured Conference on Acoustics willbe held in the following sections: multi-modal and object-oriented approachesto audition, computational acoustics, active noise control, room and buildingacoustics, and seabed acoustics.Five invited papers will be delivered by the following speakers:1. Prof. Otto von EstorffHamburg University of Technology, Hamburg;2. Prof. Grażyna GrelowskaPolish Naval University, Gdynia;3. Prof. Marek IwaniecAGH University of Science and Technology, Kraków;4. Prof. Andrzej NowickiInstitute of Fundamental Technological ResearchPolish Academy of Sciences, Warszawa;5. Prof. Anna PreisAdam Mickiewicz University, Poznań.The 58th Open Seminar on Acoustics and 2nd Polish-German StructuredConference on Acoustics together have received 115 papers. Some abstracts ofthese papers are given below.